The role of cellular crosstalk in the progression of diabetic nephropathy - Zhang, Keying; Fu, Zhangning; Zhang, Yifan; Chen, Xiangmei; Cai, Guangyan; Hong, Quan (Frontiers in Endocrinology, 2023)
Diabetic nephropathy (DN) is one of the most common complications of diabetes, and its main manifestations are progressive proteinuria and abnormal renal function, which eventually develops end stage renal disease (ESRD). The pathogenesis of DN is complex and involves many signaling pathways and molecules, including metabolic disorders, genetic factors, oxidative stress, inflammation, and microcirculatory abnormalities strategies. With the development of medical experimental techniques, such as single-cell transcriptome sequencing and single-cell proteomics, the pathological alterations caused by kidney cell interactions have attracted more and more attention. Here, we reviewed the characteristics and related mechanisms of crosstalk among kidney cells podocytes, endothelial cells, mesangial cells, pericytes, and immune cells during the development and progression of DN, and highlighted potential therapeutic.